Family Expressed Emotion in a Javanese Cultural Context - Subandi, M.A. (Springer Online, 2011)
This study aims at understanding the emotional milieu of families of psychotic patients, focusing on the concept of expressed emotion (EE). A combination of ethnographic and clinical methodology was employed. During the fieldwork in Yogyakarta, Indonesia, nine participants diagnosed as having first episode psychosis and their families were followed closely over the course of 1 year in their natural home setting. Through ongoing engagement with families, the researcher was able to gather data on the diversity of family responses to illness. Despite the fact that most families in this research could be considered to have low EE, ethnographic observation provided a more complex and nuanced picture of family relationships. This article discusses four issues concerning EE in relation to Javanese culture: the role of interpretation, the coexistence of criticism and warmth, the interpretation of boundary transgression, and the cultural concept of warmth and positive remark.